2022
DOI: 10.1108/heswbl-01-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and insights of learning process in pandemic era: a case study of South Africa

Abstract: PurposeThe Covid-19 pandemic closed most educational institutions covering all world and academic calendars are threatened. In this situation keeping academic activities live, most institutions adopted learning via online platforms. However, the question about online learning effectiveness especially in developing countries like South Africa is still not clearly or evidently recognized, as in developing countries due to technical constraints of availability of bandwidth and device suitability is a serious chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In response to the second research question, the findings indicate that students face challenges with technical reliability, resonating with literature on technology-related issues in online education (El-Masrid & Tarhini, 2017;Jung, 2019). Factors such as load shedding and poor internet access emerge as significant hurdles which aligns with studies highlighting the impact of technological barriers on e-learning effectiveness (Joaquim et al, 2022;Mpungose, 2023). This highlights the need for technological infrastructure and strategies to mitigate the effects of load shedding and ensures uninterrupted access to e-learning tools, in line with the CoI framework's emphasis on technical reliability (Garrison et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In response to the second research question, the findings indicate that students face challenges with technical reliability, resonating with literature on technology-related issues in online education (El-Masrid & Tarhini, 2017;Jung, 2019). Factors such as load shedding and poor internet access emerge as significant hurdles which aligns with studies highlighting the impact of technological barriers on e-learning effectiveness (Joaquim et al, 2022;Mpungose, 2023). This highlights the need for technological infrastructure and strategies to mitigate the effects of load shedding and ensures uninterrupted access to e-learning tools, in line with the CoI framework's emphasis on technical reliability (Garrison et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…The study identifies a crucial gap which called for a comparative analysis between factors influencing e-learning adoption in developing and developed countries (El-Masri & Tarhini, 2017). Similarly, in South Africa, Joaquim et al (2022) and Mpungose (2023) mentioned challenges and uncertainties in the shift to online learning and emphasised technical limitations and the need for improvement. Conversely, Ebrahim and Van Den Berg (2022) focused on pandemicinduced e-learning challenges that revolved around issues of motivation and engagement, heightened by the Covid-19 pandemic.…”
Section: Factors Influencing Students' E-learning Tool Preferences Fo...mentioning
confidence: 99%
“…It was also found that some students lacked the self-discipline and motivation to follow through with self-study work; and that the available resources were not conducive for online learning (Sim et al, 2021). Similar studies in the context of South Africa (Dube, 2020;Joaquim et al, 2022;Mhlanga, 2021) have reported similar findings. Meanwhile, Aristovnik et al (2020) and Wang et al (2020), reporting on the inf luence of the pandemic on students' mental health globally and in the United States (US) respectively, noted that the students described experiencing unbearable psychological pressure and feelings of boredom, anxiety, frustration and hopelessness.…”
Section: Introductionmentioning
confidence: 57%
“…Under the emergency conditions created by the Covid-19 pandemic, remote teaching allowed the continuation of distance learning throughout across various academic levels and courses. A well-designed plan of online-supported instruction enables both educators and learners to conduct lessons and continue the learning process (Joaquim et al, 2022). The paradigm shifts in achieving such an emergency transition required all the relevant support processes to be conducted through online platform.…”
Section: Digital Online Accessibility For Emergency Remote Teachingmentioning
confidence: 99%
“…Moreover, the social implications point out skills and abilities obtained through online engagement with their peers by actualising and exploring information together through inter-connectedness of sharing pathway in the online platform. In view of this, the instructor would need to give share experiences on digital environment for future education transformation (Joaquim et al, 2022). As a result, the digital learning environment could enhance the pathway of shaping future education transformation by adequately addressing possible barriers to accessibility.…”
Section: Implications Of Studymentioning
confidence: 99%